Social and political events and chaos theory: The - Filipe, J. A.; Ferreira, M. A. M. (Emerging Issues in the natural and applied sciences, 2014)
The applications of chaos theory began first by natural sciences and then follow to the humanities and social sciences. Since the beginning got rapidly a developing field. Chaos is extremely complex and difficult to be identified in the real life. But using the available information, it is possible, anyway, up to a certain extent, to find specific mathematical relationships for problems to be solved. In this work some issues are presented in order to consider this subject in the humanities and social sciences fields